Association of Age at Onset With Gray Matter Volume and White Matter Microstructural Abnormalities in People With Multiple Sclerosis. (16th November 2021) - Bonacchi, Raffaello; Meani, Alessandro; Pagani, Elisabetta; Marchesi, Olga; Falini, Andrea; Filippi, Massimo; Rocca, Maria A.
Abstract : Background and Objectives: To investigate whether age at onset influences brain gray matter volume (GMV) and white matter (WM) microstructural abnormalities in adult patients with multiple sclerosis (MS), given its influence on clinical phenotype and disease course. Methods: In this hypothesis-driven cross-sectional study, we enrolled 67 patients with pediatric-onset MS (POMS) and 143 sex- and disease duration (DD)–matched randomly selected patients with adult-onset MS (AOMS), together with 208 healthy controls. All participants underwent neurologic evaluation and 3T MRI acquisition. MRI variables were standardized based on healthy controls, to remove effects of age and sex. Associations with DD in patients with POMS and patients with AOMS were studied with linear models. Time to reach clinical and MRI milestones was assessed with product-limit approach. Results: At DD 1 year, GMV and WM fractional anisotropy (FA) were abnormal in AOMS but not in POMS. Significant interaction of age at onset (POMS vs AOMS) into the association with DD was found for GMV and WM FA. The crossing point of regression lines in POMS and AOMS was at 20 years of DD for GMV and 14 for WM FA. For POMS and AOMS, median DD was 29 and 19 years to reach Expanded Disability Status Scale score 3 ( p < 0.001), 31 and 26 years to reach abnormal Paced Auditory Serial Addition Task, 3-second version ( p = 0.01), 24 and 18 years to reach abnormal GMV ( p = 0.04), and 19 and 17 years to reach abnormal WM FA ( p = 0.36). Discussion: Younger patients are initially resilient to MS-related damage. Then, compensatory mechanisms start failing with loss of WM integrity, followed by GM atrophy and finally disability.